Entre el diletantismo y la profesionalización: Hibridez y transculturación en Las de Barranco de Gregorio de Laferrère - Carballo, Alejandra K. (Latin American Theatre Review, 2007)
At the turn of the twentieth century, as dramatic changes were occurring in Argentina in literature and the socio-political arena, Gregorio de Laferrère synthesized the historical, socio-political and cultural elements that produced local meaning. Transculturation in this essay is understood to be an issue of political positioning and selection in which two cultural systems not only coexisted but also stimulated and transformed one another. Probably more than any other literary genre, theatre proved to be one of the cultural “non-spaces” in Argentina where the two systems interacted. Moreover, Laferrère’s plays, Las de Barranco in particular, illustrate the fusion of these systems. In this paper I examine the ways in which this play underscored the fissures resulting from the confrontation and experiences of alterity between an emerging dynamic bourgeoisie and an outdated oligarchy. (AKC, Article in Spanish)